PENINGKATAN PEMAHAMAN MATA PELAJARAN FIQIH MATERI SHOLAT ID MELALUI METODE WORD SQUARE SISWA KELAS 4B MI AL-ASYHAR GRESIK - Ridlo, Meilani Aisyatur (Journal Of Islamic Elementary School (JIES), 2017)
Fiqh subjects at Madrasah Ibtidaiyah are one part of PAI subjects which are directed to prepare students to recognize, understand, appreciate and practice Islamic law, which then becomes the basis for their views of life, through guidance, teaching, and use of experience. For that students must really be able to understand the material that has been taught. However, the results of the researcher’s interview with the fiqh teacher in class 4B MI Al-Asyhar Gresik showed that out of 20 students, only 25% of students understood the material, and the rest did not understand the material. This is because the teacher does not provide a variety of methods to students. Based on the results of these interviews, researchers were encouraged to make improvements to teaching through classroom action research using the Word Square method. The improvement of students’ understanding in CAR is carried out in two cycles using a research model from Kurt Lewin’s theory, which in one cycle there are four steps, namely planning, action, observation and reflection. The research method used is descriptive quantitative and qualitative. The research subjects were students of class 4B MI Al-Asyhar. Data collection techniques used interview, observation, test and documentation techniques. Based on the results of the study, the application of the Word Square method in improving students’ understanding of the Fiqh subject of the Id Prayer material from cycle I to the next cycle went very well with the following steps: the teacher distributed activity sheets according to the existing directions, students answered questions and then shaded the letters. in the box according to the answer vertically, horizontally or diagonally, the teacher gives points for each answer in the box. In the application of the Word Square method, the results of the observation of teacher activity in the first cycle of 84.5% increased to 92.4% in the second cycle and from the results of student activities in the first cycle 79.1% increased to 90.1% in the second cycle, and an increase in student learning completeness in the Fiqh subject of the Id Prayer material from the first cycle of 70% increased to 90% in the second cycle.